Airborne and Dermal Exposure to Polycyclic Aromatic Hydrocarbons, Volatile Organic Compounds, and Particles among Firefighters and Police Investigators - Sjöström, Mattias; Julander, Anneli; Strandberg, Bo; Lewné, Marie; Bigert, Carolina (Annals of work exposures and health, 2019)
The main aim of this study was to assess dermal exposure to polycyclic aromatic hydrocarbons (PAHs) and airway exposure to PAHs, volatile organic compounds (VOCs; benzene and 1,3-butadiene), and particles among firefighters (FFs) and police forensic investigators (PFIs) in Sweden. Active (pump with a filter and sorbent tube) and passive (polyurethane foam -cyl and perkin elmer carbopack-tube) personal air sampling and dermal tape stripping (wrist and collar bone) were performed on seven FF team leaders during training fires and nine PFIs investigating the aftermath of live fire events. In addition, passive personal air sampling was performed on eight FF team leaders during live emergency fires. PAHs and VOCs were analysed using high-resolution gas chromatography low-resolution mass spectrometry. The mass concentration of total dust (particles) was determined using standard gravimetric methods. The air samples showed that the exposure to PAHs, benzene, 1,3-butadiene, and particles was below Swedish occupational exposure limits (OELs). Naphthalene was the predominant PAH in all air samples. Benzene and 1,3-butadiene were more abundant in live emergency fires, which caused higher exposures than the other studied situations. Both gaseous- and particle-associated PAHs were present on skin. The wrists seemed to be less well protected than the collarbone area. FFs and PFIs are exposed to several hazardous compounds during their work. Air exposures varied considerably between working scenarios. The observed exposures were substantially higher than urban background levels but well below Swedish OELs. The measured dermal PAH exposures were comparable to previously reported doses for US FFs but lower than the exposures reported for Swedish chimney sweeps.